E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 101 (1868); N.Y. Col. MSS, IV. 411 - (:unkn) unknown (My University, 1648)
Renewed the 1645 prohibition of trade of "any munitions of War with the Indians." Punishable by death.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES